2019
DOI: 10.1111/mbe.12190
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Individual Differences in Basic Mathematics‐Related Skills in Young Children at the Start of Formal Education

Abstract: The current study investigated the development of children's performance on tasks that have been suggested to underlie early mathematics skills, including measures of cardinality, ordinality, and intelligence. Eighty‐seven children were tested in their first (T1) and second (T2) school year (at ages 5 and 6). Children's performance on all tasks demonstrated good reliability and significantly improved with age. Correlational analyses revealed that performance on some mathematics‐related tasks were nonsignifican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…In the order task, participants have to decide if a sequence is presented in an order or not. Results from previous studies have indicated that there is a strong relation between performance on the order task and arithmetic performance in both children (Attout & Majerus, 2017;Lyons & Ansari, 2015;Lyons et al, 2014;O'Connor et al, 2018O'Connor et al, , 2019Sasanguie & Vos, 2018;Sommerauer et al, 2020;Vogel et al, 2015) and adults (Goffin & Ansari, 2016;Lyons & Beilock, 2009;Morsanyi et al, 2017;Orrantia et al, 2019;Sasanguie et al, 2017;Sella et al, 2020;Vogel et al, 2017Vogel et al, , 2019Vos et al, 2017). However, the mechanisms underlying this relationship remain relatively underspecified.…”
Section: Introductionmentioning
confidence: 99%
“…In the order task, participants have to decide if a sequence is presented in an order or not. Results from previous studies have indicated that there is a strong relation between performance on the order task and arithmetic performance in both children (Attout & Majerus, 2017;Lyons & Ansari, 2015;Lyons et al, 2014;O'Connor et al, 2018O'Connor et al, , 2019Sasanguie & Vos, 2018;Sommerauer et al, 2020;Vogel et al, 2015) and adults (Goffin & Ansari, 2016;Lyons & Beilock, 2009;Morsanyi et al, 2017;Orrantia et al, 2019;Sasanguie et al, 2017;Sella et al, 2020;Vogel et al, 2017Vogel et al, , 2019Vos et al, 2017). However, the mechanisms underlying this relationship remain relatively underspecified.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses revealed that children's performance on the NLE task was not correlated with later performance, demonstrating that the skills measured by this task may be unstable. Further results suggested the way in which children solve questions on the NLE task may qualitatively change over time (O'Connor et al, 2019). Thus, children's performance on the NLE task may reflect various other skills that develop over time, such as familiarity with numbers (Xu et al, 2021), or strategy use (Xu & LeFevre, 2016), not a single underlying numerical magnitude ability.…”
Section: Extensionmentioning
confidence: 96%
“…For example, multiple studies have shown low internal reliability for various versions of the NLE task (Hawes, Nosworthy, Archibald, & Ansari, 2019;Inglis & Gilmore, 2014;Kolkman, Kroesbergen, & Leseman, 2013). One study examined the stability of the NLE task in a sample with similar age groups and number line ranges as the current replication study (O'Connor, Morsanyi, & McCormack, 2019). Analyses revealed that children's performance on the NLE task was not correlated with later performance, demonstrating that the skills measured by this task may be unstable.…”
Section: Extensionmentioning
confidence: 99%
“…Performance on all of these measures has consistently been shown to be related to math skills (e.g., Attout et al, 2014;Attout & Majerus, 2014;Lyons & Beilock, 2011;Lyons et al, 2014;O'Connor et al, , 2019Sasanguie et al, 2017;Vos et al, 2017), although the magnitude of such relations may change developmentally (Lyons et al, 2014). Individuals with dyscalculia also show impairments on these tasks (e.g., .…”
Section: Is There a Single Order Processing Ability?mentioning
confidence: 99%
“…Most notably, we relied on a simple correlational design. Children were recruited from years 5, 6 and 7 of elementary schools, and it is likely that as children develop, and as the requirements of the school curriculum change, the most important predictors of math also change (see e.g., Lyons et al, 2014;O'Connor et al, 2019). Nevertheless, due to the relatively low number of children from each year group, it was not possible to investigate age-related changes in the contribution of each skill.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%